2018
DOI: 10.1080/03080188.2018.1453243
|View full text |Cite
|
Sign up to set email alerts
|

The social mind: disentangling affective and cognitive routes to understanding others

Abstract: To flexibly adjust behaviour to that of other people around us requires some representation of their overt actions, but also of the driving forces behind them, that is, their goals, intentions, and emotions. Socio-affective and -cognitive functions enable such representations via creating vicarious affective states in the observer (empathy) or by accumulating abstract, propositional knowledge of another person's mental state (Theory of Mind). While the empathic sharing of another's emotions is implemented by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 60 publications
2
46
0
2
Order By: Relevance
“…Of course, empathic affect sharing is only one possible response to another person's emotion. Complementary affective states such as schadenfreude, envy or compassion occur as well, but the peculiarity of empathy is that it enables access to another's internal state by re-creating a representation of that state in the observer ( 3 6 ). Correspondingly, neuroscience research on empathy has not identified one single neural network associated with empathy, but rather the brain regions found to be active depend on what affective state is shared.…”
Section: Empathy and Perspective-takingmentioning
confidence: 99%
“…Of course, empathic affect sharing is only one possible response to another person's emotion. Complementary affective states such as schadenfreude, envy or compassion occur as well, but the peculiarity of empathy is that it enables access to another's internal state by re-creating a representation of that state in the observer ( 3 6 ). Correspondingly, neuroscience research on empathy has not identified one single neural network associated with empathy, but rather the brain regions found to be active depend on what affective state is shared.…”
Section: Empathy and Perspective-takingmentioning
confidence: 99%
“…The ability to represent others' mental states, referred to as ToM or cognitive empathy, plays a critical role in understanding and navigating social situations (Frith and Frith, 2006 ). ToM represents a socio-cognitive phenomenon, involving abstract, propositional knowledge about another's mental state (Happe et al, 2017 ; Kanske, 2018 ; Preckel et al, 2018 ). Depending on the actor's approach to character performance, reflection into the character's mental life may be important part of the character creation process, involving exploration of the history, motivations, beliefs and values of the person to be portrayed, often going well beyond the information contained within the script (Noice and Noice, 2013 ).…”
Section: Theory Of Mind and Empathymentioning
confidence: 99%
“…Mental time travel can be divided into episodic memory and future thinking (Schacter, 2018;Suddendorf & Corballis, 2007). Perspective taking can be divided into affective and cognitive processes (Healey & Grossman, 2018;Kanske, 2018;Vogeley, 2017).…”
Section: Simulation Mental Time Travel and Perspective Takingmentioning
confidence: 99%